The Effectiveness of Learning Time Management in Managing Juvenile Delinquency Stress: The Moderating Roles of Parents and Schools - Puspitasari, Wahyu; Novasari, Linda; Hidayah, Nining; Souisa, Johanis (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to assess the management of school governance, focusing on the effectiveness and efficiency of study time management, and the role of collaboration between parents and the school as a moderating variable in managing juvenile delinquency stress. The research was conducted at MTSN 2 Semarang City with a sample of 75 respondents. Data analysis was performed using SPSS. The findings revealed that the effectiveness of study time management had a negative and insignificant impact on the collaboration between parents and teachers. In contrast, the efficiency of study time management was found to have a positive and significant effect on the collaboration between parents and teachers. Furthermore, the effectiveness of study time management had a significant negative impact on stress management and juvenile delinquency, while efficient study time management positively and significantly influenced both stress management and the reduction of juvenile delinquency. These results suggest that effective time management can help reduce emotional and academic stress and improve adolescent behavior. However, the study found that collaboration between parents and teachers did not significantly influence stress management or juvenile delinquency. This indicates that although effective time management can directly affect these outcomes, the collaboration between parents and teachers does not act as a mediator in this relationship. The study suggests that the collaboration between parents and teachers may be more focused on academic or disciplinary matters, rather than directly addressing stress management or juvenile delinquency.